1998
DOI: 10.1046/j.1365-2648.1998.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Living with high blood pressure

Abstract: This study was undertaken to explore the experience of people taking long-term antihypertensive medication. The study contributes to the understanding health professionals have of people with high blood pressure and the antihypertensive treatments they receive. Consideration was given to the full life context of people taking long-term antihypertensive medication and the health/medical culture in which people find themselves. A qualitative method of inquiry generated the descriptive data. Nineteen participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…PP's synthesis The four papers [134][135][136][137] focused on antihypertensive medications, with the aim of describing the experiences of patients taking these medications and providing reasons for not taking medicines as prescribed. For PP, the first published, by Morgan,134 was the 'index' paper against which the others were compared.…”
Section: Medicine-taking (Pp Lead)mentioning
confidence: 99%
See 3 more Smart Citations
“…PP's synthesis The four papers [134][135][136][137] focused on antihypertensive medications, with the aim of describing the experiences of patients taking these medications and providing reasons for not taking medicines as prescribed. For PP, the first published, by Morgan,134 was the 'index' paper against which the others were compared.…”
Section: Medicine-taking (Pp Lead)mentioning
confidence: 99%
“…For PP, the first published, by Morgan,134 was the 'index' paper against which the others were compared. Morgan's 134 publication was a book chapter, and the others were articles published in journals: nursing (two 135,136 ) and clinical (one 137 ). PP then summarised and combined the findings from each of the papers around 13 issues that she felt emerged from the papers, some of which were inter-related.…”
Section: Medicine-taking (Pp Lead)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is then important to discuss this matter with patients to help them think more carefully about the types of information they use to guide treatment decisions. Interviews with hypertensive patients revealed that adherence to treatment regimens ranged from blatant refusal to total commitment (van Wissen et al, 1998). Participants who were less adherent were those who had not identified any symptoms of hypertension.…”
Section: Background Communicationmentioning
confidence: 99%